Hubungan Penggunaan Media Pembelajaran dengan Semangat Belajar Peserta Pelatihan Bahasa Jepang - Putri, Nabilla Zainira; Jamna, Jamaris (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was based on the high of the learning spirit of Japanese language training participants at Smart College job training institute in Padang city. This assumed because of the use of learning media by the training instructors. This research aimed to: The use of learning media, the spirit of Japanese language training, and the significant relationship of the use of learning media with the spirit of Japanese language training participants. This research is a correlational quantitative study. The population in this study was all Japanese language training. The sampling technique is a cluster random sampling. The data collection technique used was a questionnaire, while the data collection tool used a questionnaire in the form of a statement list. Data analysis techniques use percentage and rank order. The results of this study indicate that: the use of instructional media is categorized quite interesting, the enthusiasm for learning Japanese trainees is categorized quite high, and there is a significant relationship between the use of learning media with the learning enthusiasm of Japanese trainees. Suggestions in this research are: it is expected that the use of attractive learning media can involve all the senses so that the material presented is clear, and appropriate for Japanese language training, it is expected that use of instructional media uses attractive colors, the material taught is in accordance with the media used, and the availability of media in training institutions, and it is expected that if the training activities use instructional media, participants will be enthusiastic in learning, on the contrary, if the training activities do not use instructional media, then the enthusiasm of participants will be less in participating in training activities.